EKSEKUSI JAMINAN FIDUSIA TANPA PUTUSAN PENGADILAN: PERSPEKTIF HUKUM DAN PRAKTIK NOTARIS - Prasetya, Danar Ikhsan; Badriyah, Siti Malikhatun (Sebelas Maret University, 2025)
Fiduciary security serves as a commonly adopted collateral mechanism in financing transactions, ensuring legal protection for creditors without necessitating their direct ownership of the collateralized asset. In practice, the execution of fiduciary security is frequently conducted without a court ruling, relying on the fiduciary certificate, which possesses executorial authority. However, with the issuance of Constitutional Court Decision No. 18/PUU-XVII/2019, the execution process has undergone substantial modifications, now requiring either mutual agreement between the creditor and debtor or the absence of any objections from the debtor. If a dispute arises, resolution must be sought through legal proceedings.This research aims to explore the execution of fiduciary security without a court ruling from a legal perspective and assess its impact on notarial practices in Indonesia. Utilizing a normative legal research approach complemented by empirical analysis, this study examines the role of notaries in drafting fiduciary security deeds and the challenges posed by regulatory shifts. Furthermore, it delves into the effects of the Constitutional Court’s ruling on legal certainty and the protection of rights for stakeholders in fiduciary agreements.The findings indicate that the Constitutional Court’s decision has brought notable changes to the fiduciary execution process, restricting creditors from enforcing security unilaterally. Consequently, notarial practices must adapt, particularly in the formulation of execution clauses within fiduciary deeds to comply with prevailing legal regulations. This study also offers recommendations to enhance the efficiency of fiduciary execution while ensuring a fair balance between the rights and responsibilities of creditors and debtors, thereby strengthening legal certainty in the financing sector.